Clinical performance of a multistep algorithm for the diagnosis of Clostridioides difficile infection and patient characteristics in a clinical setting - Khantipong, Mayuree; Sawatpanich, Ajcharaporn; Wongjarit, Kanphai; Tumwasorn, Somying; Torvorapanit, Pattama; Rotcheewaphan, Suwatchareeporn (Chulalongkorn Medical Journal, 2024)
Background: Clostridioides difficile infection (CDI) is a significant cause of antibiotic-associated diarrhea and colitis. Its diagnosis relies on clinical presentations confirmed by laboratory investigations. Objectives: This study aimed to evaluate the performance of current diagnostic tests and examine the characteristics of patients with CDI in a real hospital setting. Methods: In total, 299 unformed stool specimens were collected and analyzed using the C. DIFF QUIK CHEK COMPLETE and polymerase chain reaction (PCR) assays. Patient data were retrospectively reviewed from medical records. Results: The C. DIFF QUIK CHEK COMPLETE and PCR assays detected toxigenic C. difficile in 16/299 (5.4%) and 37/299 (12.4%) specimens, respectively. The agreement rates between these two assays for detecting C. difficile and toxin A/B were 90.3% and 93.0%, respectively. The use of a multistep algorithm with the C. DIFF QUIK CHEK COMPLETE assay, arbitrated by PCR assays, significantly increased the detection of toxigenic C. difficile (P < 0.05). Among the clinical characteristics of patients, age > 60 years was significantly associated with CDI (P < 0.05). However, the duration of antibiotic exposure and antibiotic type were not significantly different between patients with and without toxigenic C. difficile. In addition, C. difficile diagnostic tests and treatments are inappropriately used among patients presenting with diarrhea of other causes and a history of antibiotic exposure. Conclusion: A multistep algorithm is a valuable diagnostic tool for CDI, particularly in hospitals without established testing criteria. To prevent the inappropriate utilization of laboratory resources, effective stewardship of C. difficile testing is essential.